Penggunaan Media Video Animasi Dalam Meningkatkan Nilai Belajar Bahasa Indonesia Peserta Didik Kelas Iii Di Sekolah Dasar Negeri 06 Pontianak Utara - Dinda Aprillia; Nelly Mujahidah; Resvan Resvan (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2026)
The purpose of this study was to analyze: (1) To describe the learning achievement of students in the control class without using animated video media. (2) To describe the application of animated video learning media in the experimental class. (3) To describe the effect of using Animated Video Media in the control class and experimental class of North Pontianak State Elementary School. This research includes quantitative research experimental method. The data sources of this research are population and sample. The population in this study were all grade 3 students of SDN 06 North Pontianak. The sample in this study consisted of 2 classes with each class totaling 20 students. Based on the analysis conducted, the researchers concluded that: (1) The pre-test results of the control class there were 9 people who were complete, according to the KKM value of 75 while the other 11 people did not complete or get a score below the KKM. The average value obtained is 65. (2) The use of animated video media in Indonesian language learning in Chapter 2 Friends Along has been carried out as the steps set out in the teaching module with 100% implemented. (3) In the hypothesis test of the post-test data of the control and experimental classes, the results obtained a value (Sig) of 0.001, which means the value (Sig)> 0.05 and shows that there is an average difference between the experimental class and the control class so that there is an influence of the independent variable on the dependent variable.